Analysis of listening learning strategies and its incidence in listening skill performance in students of second baccalaureate at Unidad Educativa Milagro 2017 - 2018. - Zúñiga Navarrete, Mirian Magdalena (2020)
The present study reports how listening skill performance is related to the amount of listening learning strategies applied by students of second baccalaureate at Unidad Educativa Milagro. A sample of 150 students participated in this research during school year 2017 – 2018 through a quantitative method using three different data collection techniques: evaluation, survey and class observations. All of them were applied in a sequential process, analyzed separately the cognitive, metacognitive and socio-affective strategies, and the final results were classified in low, moderated and high level of proficiency in listening skill according to the amount of listening learning strategies the students applied in class. The investigation concluded that listening learning strategies and listening skill performance are directly proportional variables. Furthermore, to increase the practice of strategies in students and to improve their proficiency in listening, at the end of the investigation there is a website proposal especially elaborated for this sample of English language learners with selected activities that put in practice several listening learning strategies.